Dangerous strait : the U.S.--Taiwan--China crisis - Tucker, Nancy Bernkopf (Columbia University Press, 2005)
Today the most dangerous place on earth is arguably the Taiwan Strait, where a war between the United States and China could erupt out of miscalculation, misunderstanding, or accident. How and to what degree Taiwan pursues its own national identity will have profound ramifications in its relationship with China as well as in relations between China and the United States. Events late in 2004 demonstrated the volatility of the situation, as Taiwan's legislative elections unexpectedly preserved a slim majority for supporters of closer relations with China. Beijing, nevertheless, thr.